Modulation of innate lymphoid cells by enteric bacterial pathogens - Sah, Prakash; Zenewicz, Lauren A. (Frontiers in Immunology, 2023)
Innate lymphoid cells (ILCs) are key regulators of tissue homeostasis, inflammation, and immunity to infections. ILCs rapidly respond to environmental cues such as cytokines, microbiota and invading pathogens which regulate their function and phenotype. Even though ILCs are rare cells, they are enriched at barrier surfaces such as the gastrointestinal (GI) tract, and they are often critical to the host's immune response to eliminate pathogens. On the other side of host-pathogen interactions, pathogenic bacteria also have the means to modulate these immune responses.Manipulation or evasion of the immune cells is often to the pathogen's benefit and/or to the detriment of competing microbiota. In some instances, specific bacterial virulence factors or toxins have been implicated in how the pathogen modulates immunity. In this review, we discuss the recent progress made towards understanding the role of non-cytotoxic ILCs during enteric bacterial infections, how these pathogens can modulate the immune response, and the implications these have on developing new therapies to combat infection.